Analysis of the Legality of Unjust Laws from the Perspective of Positivist Theory Through a Case Study of Alice in Borderland - Chitjuy, Theewara; Rattanathai, Parinda; Satapoomin, Phitchaya; Shoosanglertwijit, Pimlada; Morakotsriwan, Methisa; Prempongsawat, Saengdao (Nitiparitat Journal, 2024)
This article aims to analyze a case study from the Japanese series “Alice in Borderland” Season 1 by examining the actions of the main character, Arisu, who strives to survive in a deadly parallel world along with other players through a series of games. Each game is controlled and regulated by an authority from above, and each player must follow these rules, including killing each other to survive, which is not considered illegal. Due to societal pressure, Arisu is compelled to follow the game rules despite internal conflict. Meanwhile, some other players feel that killing is not wrong, leading to a conflict between the enforcement of laws or commands and morality. The authors believe that the legal philosophy issues presented in the series are particularly suitable as a case study for considering the legality of the commands of supreme authority in this given situation. They aim to examine whether the rules derived from such authority are considered laws through the perspectives and legal theories of positivist philosophers such as John Austin and H.L.A. Hart and analyze the limitations of these philosophers’ legal theories.